Autophagy Improves Inflammatory Response in Sepsis Accompanied by Changes in Gut Microbiota - La Wang; WenJia Wang; GuiTong Jiang; ZunLi Ke; RuiXi Luo; WeiYi Tian (Hindawi Limited, 2024)
Conclusion: Autophagy is able to improve inflammation and may directly or indirectly regulate the microbiota of septic rats. Autophagy may be an important target for future clinical interventions in the treatment of sepsis.